TRANSFORMATION OF STUDY CLUB INTO POLITICAL PARTY: RADICALISM OF DEMOCRATIC PEOPLE PARTY IN INDONESIA - Argenti, Gili (Jurnal Politikom Indonesiana, 2018)
Abstract In the New Order era, in the late 1970s and early 1990s, the student movement was confronted with repressive actions by the government, a policy to restrict students’ political activities. So the search for a new format of movement is a necessity, the study group is chosen as a new format of student movement. This research explains how the process of changing the formation of student movements from the study group to the Democratic People Party (PRD), as well as explaining the radical political activities of the PRD from the New Order until post-reform. This study is a literature study using written data. The objective of the study was to raise the role of non-mainstream party politics in the contemporary Indonesian political stage. In the context of the social movement that became the object of this study, transformation takes place in several forms. First, the change from study groups that examine critical social literature and marxism, underground, transformed into a "formal institution" movement in the form of an Action Committee and a non-governmental organization (NGO). Second, the change from the Committee of Action and Non-Governmental Organizations into a political party (PRD). Third, the change of movement format from the "resistance" party to the electoral party after the fall of the New Order government. And Fourth, change back into social movement of political party. Keywords: Democratic People Party; Radicalism; Social Movements; Study club.